Properties Around the First Eigenvalue of a Partial Discrete Dirichlet Boundary Value Problem (Journal of Nonlinear Modeling and Analysis, 2025)
In this article, we study some results around the first eigenvalue $λ_{1,m}$ for the partial discrete Dirichlet boundary value problem, like the constant sign of the eigenfunction associated with $λ_{1,m}$, the simplicity of $λ_{1,m}$ and the sign change of any eigenfunction associated with $λ > λ_{1,m}$.